The Prognostic Significance of the age-adjusted Charlson Comorbidity Index in the Prediction of Postoperative Outcome after Liver Resection for Colorectal Cancer Metastases - Djordjic, Anastasia; Bogdanovic, Professor Aleksandar; Zdujic, Predrag; Djindjic, Uros; Basaric, Dragan; Dugalic, Vladimir (Medical Research, 2024)
Introduction: The prognostic value of the age-adjusted Charlson comorbidity index (ACCI) for patients with colorectal liver metastases (CRLM) undergoing liver resection is still unclear. The aim of this study is to analyze the impact of ACCI in the prediction of short- and long-term outcomes after liver resection in patients with CRLM.Material and methods: Data related to 101 patients who underwent liver resection for CRLM at the University Clinic for Digestive Surgery between October 2019 and October 2022 were analyzed retrospectively. ACCI was determined according to an established point scale. Patients were further divided into two groups: group 1, ACCI
Keywords: colorectal cancer; liver metastases; Charlson comorbidity index